People VS Bureaucracies in the 2020’s - Avny, Amos (IJRDO-Journal of Applied Science, 2015)
The world of 2020’s differs significantly from the previous century. It is natural, therefore, that people will call for changing also the Public Administration and all the governance establishment. The paper below discusses some paradigmatic changes required for improving the existing system. Further, it explores the direct and non-direct democratic way of representation, which can be improved by using the new advanced communication technology. Later the Author shortly discusses the E-Government future potential. He also emphasizes his recommendation for making public service a much more people oriented and human centric system. Finally, the Author suggests to introduce into the existing bureaucracies a mandatory by-pass mechanism that will enable circumventing most of the system’s unnecessary built-in obstacles. The mandatory by-pass mechanism will be built of two levels exceptional committees, one at the field level and one of the appeal one and will be staffed by current and retired employees.